Residencia de Medicina Física y Rehabilitación en el Perú: número de vacantes y análisis de los planes de estudios - De la Cerna-Luna, Roger (2023)
Introduction. In Peru there is a shortage of physiatrists, and the standards for the training of specialists in Physical Medicine and Rehabilitation (PM&R) have not been updated since 2002. There are no studies that have focused on this problem. Objectives. To describe the number of PM&R positions and analyze the PM&R residency programs’ curriculums. Methods. Descriptive observational study. We reviewed the number of PM&R positions offered in the 2017-2022 period. Likewise, we collected the variables of interest from the curriculums that offer this residency program, including the approach of 30 basic competencies recommended by the International Society of PM&R (ISPRM). Results. During the 2017-2022 period, 11 universities offered 283 PM&R positions, of which 89.4% corresponded to the city of Lima. The number of positions showed a downward trend from 2018 to 2021. 7/11 curriculums addressed at least 75% of the basic competencies recommended by the ISPRM, and none of them addressed 100% of these competencies. In addition, we found heterogeneity between universities respect to the theoretical courses taught, the number of academic credits and the external rotations allowed. Conclusions. In Peru, the number of PM&R positions decreased during the COVID-19 pandemic, despite its crucial role in caring for the affected population and the shortage of physiatrists. No curriculum includes all the basic competencies recommended by ISPRM, highlighting the need to update and restructure them.